Rancang Bangun Website Sekolah Dasar Negeri 2 Tlogorandu - Melinda Deafani; Febrianta Surya Nugraha; Tinuk Agustin (PT. Pustaka Cendekia Publisher, 2024)
The purpose of this study is to design a school profile website to be instructed by a school engineer. The study was conducted in SD Negeri 2 Tlogorandu and aimed to develop a website as a medium for widespread dissemination of information that plays an important role in improveing productivity, especially in the field of education. The statistics accumulating method used was qualitative and used the Rapid Application Development (RAD) method. The Study also included a SWOT (Strength, Weakness, Opportunities, Threats) analysis method. The results of this study showed that the design and development of a school website can help schools disseminate information in a more convenient and efficient manner, especially about the admission of new students. According to the result, the website has been successfiully created to allow schools to easily transfer and manage the latest statistics or information, thusly meeting the necessity of the school.